Serratia spp. as plant growth-promoting bacteria alleviating salinity, drought, and nutrient imbalance stresses - Kulkova, Iryna; Wróbel, Barbara; Dobrzyński, Jakub (Frontiers in Microbiology, 2024)
In agricultural environments, plants are often exposed to abiotic stresses including temperature extremes, salt stress, drought, and heavy metal soil contamination, which leads to significant economic losses worldwide. Especially salt stress and drought pose serious challenges since they induce ionic toxicity, osmotic stress, and oxidative stress in plants. A potential solution can be the application of bacteria of the Serratia spp. known to promote plant growth under normal conditions Thus the mini-review aims to summarize the current knowledge on plant growth promotion by Serratia spp. (under the conditions of salinity stress, drought, and nutrient deficit) and highlight areas for development in the field. So far, it has been proven that Serratia spp. strains exhibit a variety of traits contributing to enhanced plant growth and stress tolerance, such as phytohormone production, ACC deaminase activity, nitrogen fixation, P and Zn solubilization, antioxidant properties improvement, and modulation of gene expression. Nevertheless, further research on Serratia spp. is needed, especially on two subjects: elucidating its mechanisms of action on plants at the molecular level and the effects of Serratia spp. on the indigenous soil and plant microbiota and, particularly, the rhizosphere. In both cases, it is advisable to use omics techniques to gain in-depth insights into the issues. Additionally, some strains of Serratia spp. may be phytopathogens, therefore studies to rule out this possibility are recommended prior to field trials. It is believed that by improving said knowledge the potential of Serratia spp. to stimulate plant growth will increase and strains from the genus will serve as an eco-friendly biofertilizer in sustainable agriculture more often.